Effect of mineral reaction between calcium and aluminosilicate on heavy metal behavior during sludge incineration. (1st October 2018) - Zha, Jianrui; Huang, Yaji; Xia, Wenqing; Xia, Zhipeng; Liu, Changqi; Dong, Lu; Liu, Lingqin
Highlights: Effects by calcium were different between copper and zinc during sludge incineration. Two retention forms for heavy metal in ash were clarified to reveal the transference of heavy metal. The volatile and retention forms of heavy metals were changed with increasing additive or temperature. Reaction between calcium and aluminosilicate impacted on the behavior of heavy metal. The correlation between mineral reaction and heavy metal behavior was demonstrated. Abstract: Calcium-based additives such as lime, portlandite and limestone are widely applied in solid waste incineration for desulfurization. However, calcium may affect emission of heavy metals. In this study, effects of mineral reaction on the transference of copper and zinc during sludge combustion are investigated. Sludge from a chemical fiber factory was blended with lime as an additive in different mass fractions. The incineration tests were performed in a tube furnace at temperatures of 600–1100 °C. Then the ash was digested into two methods to clarify two retention forms of heavy metals. The X-ray diffraction shows that the calcium from additive converted to calcite, amorphous calcium, gehlenite and anorthite successively as temperature rising. The two-step digestion reveals that minerals above change the distribution of heavy metals between different forms. The residual form of both two heavy metals increases with temperature upgraded, while the leachable form presents an opposite trend. Calcium stimulated the volatility of copper at all temperatures but took positive effect on volatility of zinc only at 600 °C and promoted its retention at higher temperatures. With consideration of retention forms, mineral composition and temperature, it is suggested that through reactions with aluminosilicate, calcium changes heavy metals transference to a different extent. Competition by calcium to produce aluminosilicate inhibits retention of heavy metals, but zinc can be together with calcium as eutectic aluminosilicate at higher temperatures. Surface morphologies were detected by scanning electronic microscopy and energy dispersive spectrometer, confirming the effect of calcium.